1997
DOI: 10.1111/j.1439-0450.1997.tb00960.x
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Survey for Antibodies toBorrelia burgdorferiin Sheep, Goats and Dogs in Cordillera Province, Bolivia

Abstract: Summary A serosurvey for antibodies to Borrelia burgdorferi using an enzyme‐linked immunosorbent assay (ELISA) was conducted on sheep, goat and dog serum samples collected in Cordillera Province, Bolivia, in 1992. Sera from 98 sheep, 218 goats and 43 dogs were tested. The observed seroprevalence in sheep and dogs was 0.0%, whereas the seropositivity rate for goat serum samples was 5.0%. Upon analysing 10 positive sera by Western immunoblotting, five reacted against the specific protein antigens and all of them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 7 publications
3
10
2
2
Order By: Relevance
“…However in another study from the same region positivity was only 15.38 % (Savaliya and Pal, 2008). These findings clearly indicated that the rate of seroprevalence is not consisted and varies at different time intervals supporting the earlier findings reported from Nigeria (Agunloye 2002), Bolivia (Ciceroni et al, 1997), Egypt (Maronpot and Barsoum 1972), Brazil (Martins et al, 2012;Higinoa et al, 2013), Iran (Hassanpour et al, 2012) and Malaysia (Bahaman et al, 1987;Samsi Suhaila et al, 2013).…”
Section: Resultssupporting
confidence: 88%
“…However in another study from the same region positivity was only 15.38 % (Savaliya and Pal, 2008). These findings clearly indicated that the rate of seroprevalence is not consisted and varies at different time intervals supporting the earlier findings reported from Nigeria (Agunloye 2002), Bolivia (Ciceroni et al, 1997), Egypt (Maronpot and Barsoum 1972), Brazil (Martins et al, 2012;Higinoa et al, 2013), Iran (Hassanpour et al, 2012) and Malaysia (Bahaman et al, 1987;Samsi Suhaila et al, 2013).…”
Section: Resultssupporting
confidence: 88%
“…However, the same study (3) reported that dogs had never been evaluated as carriers of Leptospira in Egypt, and the observed seroprevalence in that study was 12%, which was similar to the seroprevalence reported in Italy (20) and Thailand (21) but much lower than that reported in Germany (22) , Mexico (23) and the USA (24) . The same study found a high seroprevalence of leptospires in cows (44%).…”
Section: Table 3 -Results Of Serotyping Of the Isolates Recovered Frosupporting
confidence: 75%
“…This value is similar to that described in Italy 19 and Thailand 28 ; however, it is much less than that reported in Germany, 29 Mexico, 30 and the United States. 31 No particular serovar was predominant in our study, although other reports have claimed a more frequent distribution of serovars Grippotyphosa, Icterohaemorrhagiae, Australis, and Canicola.…”
Section: Discussionsupporting
confidence: 58%
“…10 This discrepancy may be caused by differences in localities screened, number of animals used, or laboratory testing methods. Worldwide, the reported prevalence of leptospirosis in sheep has been comparatively low in Canada, 16 Portugal, 17 Chile, 18 Italy, 19 and Brazil. 20 However, Ciceroni and others 19 claimed that carrier sheep in Italy had atypical serovars (e.g., serovar Poi) that have not been looked for in this study and rarely elsewhere.…”
Section: Discussionmentioning
confidence: 99%